Influence of microwave sterilization on the cutting capacity of carbide burs - Grassi Fais, Laiza Maria [UNESP]; Pereira Pinelli, Ligia Antunes [UNESP]; Adabo, Gelson Luis [UNESP]; Barbosa Tavares da Silva, Regina Helena [UNESP]; Marcelo, Caroline Canhizares [UNESP]; Guaglianoni, Dalton Geraldo [UNESP] (Universidade de São Paulo (USP), Faculdade de Odontologia de Bauru, 2009)
Objective: This study compared the cutting capacity of carbide burs sterilized with microwaves and traditional sterilization methods. Material and Methods: Sixty burs were divided into 5 groups according to the sterilization methods: dry heat (G1), autoclave (G2), microwave irradiation (G3), glutaraldehyde (G4) or control - no sterilization (G5). The burs were used to cut glass plates in a cutting machine set for twelve 2.5-min periods and, after each period, they were sterilized (except G5) following the protocol established for each group. The cutting capacity of the burs was determined by a weight-loss method. Data were analyzed statistically by Kruskal-Wallis and Dunn's test. Results: The means of the cutting amount performed by each group after the 12 periods were G1 = 0.2167 +/- 0.0627 g; G2 = 0.2077 +/- 0.0231 g; G3 = 0.1980 +/- 0.0326 g; G4 = 0.1203 +/- 0.0459 g; G5 = 0.2642 +/- 0.0359 g. There were statistically significant differences among the groups (p<0.05); only dry heat sterilization was similar to the control. Conclusion: Sterilization by dry heat was the method that least affected the cutting capacity of the carbide burs and microwave sterilization was not better than traditional sterilization methods.
Keywords: Sterilization; Dental instruments; Infection control; Microwaves